Unused cars in Wroclaw – in terms of using city space - Szulc, Anna (Nieużytkowane samochody we Wrocławiu – aspekt wykorzystania przestrzeni miejskiej, 2020)
Excessive traffic and the insufficient number of parking spaces pose a challenge for the authorities of large urban centres, which is why it is important to effectively use the infrastructure resources. An example of actions that reduce efficiency regards unused cars in public parking. The discussed problem should be considered in the context of the impact on spatial order, and the phenomenon of misappropriation of public space. This article analyses Mobility Policy of the City of Wroclaw and data on the intervention of the Municipal Police of Wroclaw regarding the disposal of unused vehicles according to article 50a and 130a of Road Traffic Law. An integral part of the article is a survey examining the opinions of the local community. Unused cars have a negative impact on the quality of space and life of residents, which is manifested by a decrease in the efficiency of transport infrastructure, degradation of green areas, appropriation of public space and disturbance of spatial order
Biblioteka Regionalisty, 2020, Nr 20, s. 153-169
Keywords: unused cars; parking policy; interventions of Municipal Police; city; spatial order; nieużytkowane samochody; polityka parkingowa; interwencje Straży Miejskiej; miasto; ład przestrzenny